Social Transformation in Maluku: The Impact of External Migration on Local Community Dynamics - Suleman Watianan (Westscience Press, 2023)
This research aims to explore social transformation in the Maluku Island, with a focus on the impact of external migration on the dynamics of the local community in the city of Ambon. The research method employed is a literature review, allowing for an in-depth examination of the conceptual framework, previous findings, and historical developments that have shaped the social conditions of this city. The literature review includes the search and analysis of sources such as books, journal articles, theses, and research report relevant to the research topic. The historical and cultural context of the Maluku Island becomes the focus to understand the roots of social transformation. The analysis of patterns of external migration, migrant motivations, and their impact on the structure of the local community is a primary highlight. The results of the literature review identify complex patterns of social transformation involving changes in cultural values, social structures, and interactions between the indigenous population and migrants. Social integration, challenges, and opportunities are identified through an understanding of the dynamics of intergroup relationships. This research also compares literature findings on social transformation due to migration in the Maluku Island with similar research in other regions, enriching cross-regional understanding of migration impacts. Through the literature review approach, this research provides a comprehensive foundation for understanding social transformation in the Maluku Island and contributes to academic literature related to external migration. The implications of the research findings are expected to support the development of more effective policies and strategies in managing social dynamics in the city of Ambon.